Islamic Educational Values in the Marriage Traditions of the Javanese, Banjar, and Bugis Ethnic Groups in Indonesia: A Systematic Literature Review - Rosita Rosita; Khojir Khojir; Ida Suryani Wijaya; Agus Setiawan (SYAMIL: Journal of Islamic Education, 2025)
This study aims to identify Islamic educational values within the marriage traditions of the Javanese, Banjar, and Bugis ethnic groups in Indonesia, which are rich in culture and local wisdom passed down through generations. A systematic literature review was conducted using accredited articles published between 2017 and 2023, collected from Google Scholar, Harzing's Publish or Perish, and Publish Media. The researchers initially gathered 20 articles, which were then analyzed and synthesized, resulting in 7 articles that met the criteria and were relevant to the research questions. Based on the analysis and literature review, several conclusions can be drawn. First, the marriage traditions of the Javanese (such as ngelamar, nontoni, menimbang, paningsetan, dhahar kembul, ngindek telur, wijik sekar setaman, kacar-kucur, baling bantal, tukar kembar mayang, and sungkeman), the Banjar (such as basasuluh, badatang, bapayuan, maantar patalian, bapingit, bakasai, batimung, bainai, and batamat Al-Qur’an), and the Bugis (such as mammanu-manu, massuro, mappasiarekeng, cemme passili, mappacci, mappenre botting, ijab kabul, mappasiluka, amrola, mammatoa, and marola wekke dua) are still practiced as a form of cultural and religious responsibility, though they are now often simplified to save time. Second, these marriage traditions reflect the internalization of Islamic educational values, including values of faith (iman), worship (ibadah), ethics (akhlak), and social responsibility. This study acknowledges its limitations in terms of the number of analyzed articles, especially those published in SINTA-accredited journals.